Molecular Neuropathology in Practice: Clinical Profiling and Integrative Analysis of Molecular Alterations in Glioblastoma - MacLean P. Nasrallah MD, PhD; Zev A. Binder MD, PhD; Derek A. Oldridge MD, PhD; Jianhua Zhao PhD, FACMG; David B. Lieberman MS, CGC; Jacquelyn J. Roth PhD; Christopher D. Watt MD, PhD; Shrey Sukhadia MS; Eva Klinman PhD; Robert D. Daber PhD; Arati Desai MD; Steven Brem MD; et al. (Elsevier, 2019)
Molecular profiling of glioblastoma has revealed complex cytogenetic, epigenetic, and molecular abnormalities that are necessary for diagnosis, prognosis, and treatment. Our neuro-oncology group has developed a data-driven, institutional consensus guideline for efficient and optimal workup of glioblastomas based on our routine performance of molecular testing. We describe our institution's testing algorithm, assay development, and genetic findings in glioblastoma, to illustrate current practices and challenges in neuropathology related to molecular and genetic testing. We have found that coordination of test requisition, tissue handling, and incorporation of results into the final pathologic diagnosis by the neuropathologist improve patient care. Here, we present analysis of O 6 -methylguanine-DNA-methyltransferase promoter methylation and next-generation sequencing results of 189 patients, obtained utilizing our internal processes led by the neuropathology team. Our institutional pathway for neuropathologist-driven molecular testing has streamlined the management of glioblastoma samples for efficient return of results for incorporation of genomic data into the pathological diagnosis and optimal patient care.